Penegakan Hukum Kasus Jual Beli Organ Tubuh di Indonesia - Ruslan Abdul Gani; Yudi Armansyah (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2016)
This research attempts to reconstruct the law enforcement issues related to the case of human organs trade in Indonesia. As we know, the rules of law related to the prohibition of the sale and purchase or illegal transplantation of organs has been issued by the government. But the fact does not make organized crime vanished. Therefore, it is necessary to have the latest reformulation that can realize to the root of the problem. One of them is by integrating between Islamic law in the form of the products fiqh and the Health Act (Act No. 36 of 2009). This research is normative juridical research. Its focus is directed on the study of theorem, principle, conception, legal doctrine and content rules of positive law. It is analyzed descriptively and qualitatively by reducing the data, presenting the data and draw conclusions. Both Islamic law and health law equally prohibits the practice of buying and selling of organs strictly in principle. It is because of the high risk of illegal actions against a person's health, due to the lack of health standards in the black market organ sales. Organs will no longer work when it is transplants for living donor. Interestingly, both Islamic law and the laws of health go hand in hand in an effort to prevent the practice of buying and selling of organs, especially the highly dynamic Islamic law to follow the development of humanity. This is evident from the birth of some of the Fatwa (a binding ruling in religious matters) issued by the Indonesian Mufti Council (MUI) that related to the issue of human organs. Similarly, Health Act is very appropriately referred to as human rights laws because many provide humanitarian protection in the field of health.